Analisis Gaya Belajar Siswa Berprestasi di SD Negeri 5 Tolitoli - Nuralan, Sitti; Ummah BK, Muh. Khaerul; Haslinda, Haslinda (Pengembangan Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
This study aims to : (1) determine the learning styles of outstanding students in class V Aof SD Negeri 5 Tolitoli; (2) to know the supporting and inhibiting factors of the outstanding students in class V A of SD Negeri 5 Tolitoli. This type of research is a qualitative research, where in collecting data using observation interview, and documentation teshniques. The data analysis techniques used are data reduction, data presentation, conclusion drawing and verification. The results of this study indicate that thelearning styles of outstanding students at SD Negeri 5 Tolitoli can be implemented effectively through 3 indicators, namely visual learning styles, auditory learning styles and kinesthetic learning styles, while those that cannot be separated from the supporting and inhibiting factors at SD Negeri 5 Tolitoli